Partially covered self-expandable metal stent with antimigratory single flange plays important role during EUS-guided hepaticogastrostomy - Yamamura, Masahiro; Ogura, Takeshi; Ueno, Saori; Okuda, Atsushi; Nishioka, Nobu; Yamada, Masanori; Ueshima, Kazuya; Matsuno, Jun; Yamamoto, Yoshitaro; Higuchi, Kazuhide (Endoscopy International Open, 2022)
Background and study aims Stent migration into the abdominal cavity, which can occur due to stent shortening or stomach mobility, is a critical adverse event (AE) in EUS-HGS. To prevent this AE due to stent shortening, a novel, partially covered self-expandable metal stent with an antimigratory single flange has recently become available in Japan. The present study evaluated the clinical feasibility and safety of EUS-HGS using this novel stent.Patients and methods We measured stent length in the abdominal cavity and the luminal portion after EUS-HGS using computed tomography (CT) performed 1 day after EUS-HGS (early phase). To evaluate stent shortening and the influence of stomach mobility, we also measured stent length at the same sites on CT performed at least 7 days after EUS-HGS (late phase).Results Thirty-one patients successfully underwent EUS-HGS using this stent. According to CT in the early phase, stent length in the abdominal cavity was 7.13 ± 2.11 mm and the length of the luminal portion was 53.3 ± 6.27 mm. Conversely, according to CT in the late phase, stent length in the abdominal cavity was 8.55 ± 2.36 mm and the length of the luminal portion was 50.0 ± 8.36 mm. Stent shortening in the luminal portion was significantly greater in the late phase than in the early phase (P = 0.04).Conclusions CT showed that stent migration can occur even with successful stent deployment, due to various factors such as stent shortening. The antimigratory single flange may be helpful to prevent stent migration, but further prospective comparative studies are needed to confirm our results.